Specificity of antibodies established from mammals in rainbow trout (Oncorhynchus mykiss). (2nd February 2013) - Grunow, B.; Böhmert, B.; Fechner, K.
Summary: This study deals with the question as to whether antibodies established for mammals are also specific for rainbow trout. The reason for this examination is the major economic importance of rainbow trout in aquaculture and the growing scientific attention. However, there are few primary antibodies so far defined for this fish species. Therefore, the aim of the current study was to test the ability of 15 commercially available antibodies for rainbow trout in an indirect immunofluoresence assay to analyse tissue sections of organs. Five commercially available primary antibodies were identified, which were directed against proteins of one or two organs/ cell types in rainbow trout.